Short-term electrocardiographic atrial remodelling after asd closure with the gco device in a pediatric population. (19th May 2022) - Fumanelli, J; Garibaldi, S; Castaldi, B; Di Candia, A; Cuman, M; Pizzuto, A; Sirico, D; Mirizzi, G; Piacenti, M; Cantinotti, M; Assanta, N; Di Salvo, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Aim: The GORE® CARDIOFORM septal occluder (GCO) is an atrial septal defect/patent foramen ovale (ASD/PFO) closure device with theoretical advantages over other commercialized devices thanks to its softness and anatomical compliance. Our aim was to evaluate the short and medium-term electrocardiographic changes after percutaneous ASD closure with GCO in a pediatric population. Methods: We enrolled 39 patients with isolated ASD submitted to trans-catheter closure with GCO from January 2020 to June 2021. EKG was performed before (T0), at 24 hours (T1) and 6 months (T2) after ASD transcatheter closure. P wave dispersion was calculated as the difference between maximum and minimum P- wave duration, PR interval as the interval between beginning of the P wave and beginning of the QRS complex and QT dispersion as the difference between maximun and minimun of QTc intervals. At 6-months from device implantation, the patients were submitted to ambulatory EKG Holter recording. Results: Patients' age and BSA were 8.2±4.2 years (IQR 4.2-8.3, median 7.0) and 1.0±0.3 m2 (IQR 0.7-1.7, median 0.9), respectively. The strectched ASD diameter was 16.3±4.5 mm (median 16), resulting in QP/QS of 1.7±0.6 (median 1.5). At the baseline mean P wave dispersion was 40±15 msec and decreased to 30±13 msec (p<0.002) at 24h, without any further change at 6 months (30±13 msec, p<0.002). PR conduction significantly improved at 24 h from device implantation (from 175.0±20.8 to 144.0±22.7 msec, p=0.018) and did not significantly change at 6 months (164.0±19.5 msec, p=NS). QTc dispersion decreased at 24 hours (31.7±.20.3, p<0.02) and at 6 months (28.0±18.1, p<0.002) from device implantation. After device deployment, 2 pts (5%) developed transient, self-limited junctional rhythm and one of them needed a short course of anti-arrhythmic therapy for supra-ventricular tachycardia. No tachy/brady-arrhythmias were recorded at the 6-months follow-up EKG Holter monitoring. Conclusions: Percutaneous ASD closure with the GCO device results in significant, sudden improvement of intra-atrial, atrio-ventricular and intraventricular electrical homogeneity. This benefit persists unaltered over a medium term follow-up. It might be due to a favourable volumetric remodelling that was not hindered by mechanical impact of the occluding prosthesis and could explain the low rate of arrhythmias found at the mid-term EKG evaluation.